Penerapan Teknik Taking Notes untuk Meningkatkan Kemampuan Membaca Mahasiswa PBA IAIM NU Metro Lampung - syaifullah, muhammad (LISANIA: Journal of Arabic Education and Literature, 2018)
This study aims to describe the learning implementation of Arabic text reading with cognitive strategies of taking notes techniques and to describe the results of increased mastery of Arabic text reading of Arabic Education students at IAIM NU Metro Lampung through the use of cognitive strategies with taking notes techniques. This research is conducted at IAIM NU Metro Lampung. The research subjects are students in the fourth semester of the 2017/2018 academic year, totaling 11 students. The research design uses Classroom Action Research, namely planning, implementation, observation and reflection. This research is conducted in 2 cycles, with 2 meetings each cycle. The instruments used are test questions, observation sheets and interview guidelines. The results show that: (1) the ability of students to read Arabic texts with taking notes techniques has increased. At the first meeting of the first cycle, it is found that in the loud reading session, most students are less total in making a vote, but at the second meeting there has been an increase. (2) students also feel helped in understanding the contents of Arabic text by taking notes techniques because this technique is very simple and easy to apply. From the data obtained, it is known that the ability of students to understand the Arabic text has increased, namely before the action of student learning outcomes is carried out on average only 45% after the end of the action in the first cycle an average of 79%, and cycle II an average of 86% .